Prácticas de enseñanza de iniciación a la lecto escritura en el primer año de educación general básica en la Unidad Educativa Miguel de Cervantes Saavedra - Loachamin Andrango, Carolina Sandy (2016)
This case study aims to analyze pedagogical practices in initiation to literacy in the first year of General Basic Education in the Education Unit Miguel de Cervantes Saavedra. The main objective is to analyze teaching practice in their daily lives as suggested (Litwin, 2008), reviewing the application of knowledge possessed by the teacher, methods, strategies, resources, teaching materials and interaction between teacher and student, all this has a theoretical support from several authors such as Piaget, Vygotsky, Freire, Ausubel, under these theories allows us to analyze and reflect on whether the contributions that these authors provided or not applied in the classroom. The methodology used for this analysis was qualitative, ethnographic method, for which there has been a participant observation, data were recorded in a field diary and observation a tab for later analysis. So the research also breaks down all the categories that have been studied in observation instruments such as planning, teaching-learning, teacher-student interaction, learning experiences, types of academic tasks and finally strategies evaluation, thus allows a critical and reflective study on teaching practice. The main results of this analysis show that the method used by the teacher in the process of initiation was phonetic literacy.